Remedies, analysed - Steel, S (Oxford University Press, 2020)
While an extensive literature exists on the nature and justification of particular remedies, such as compensation or restitution, the nature and justification of remedies in general is less well explored. This article reviews Stephen Smith’s Rights, Wrongs, and Injustices: The Structure of Remedial Law, which offers an account of the nature of remedies, why courts award them, and a taxonomy of the grounds of private law remedies. The article considers the following questions addressed or raised by the book: (i) What is a remedy? (ii) Why do courts grant remedies? (iii) What are the grounds of remedies? and (iv) Should remedial law be considered an area of law? Each section sets out and analyses Smith’s answers and some alternative views are outlined. For example, I sketch a different account of the concept of a remedy which is not restricted to rulings, refine the book’s account of the distinction between substantive and remedial law, and offer reasons to doubt that the grounds of remedies are fully reducible to wrongs, injustices and Right threats.